2015
DOI: 10.1002/qua.24877
|View full text |Cite
|
Sign up to set email alerts
|

Fluorines in tetrafluoromethane as halogen bond donors: Revisiting address the nature of the fluorine'sσhole

Abstract: It has been demonstrated in several instances that the 0.001 a.u. (electrons per bohr3) isodensity mapped electrostatic surface potentials on the fluorines along the outermost extensions of the CF covalent bonds in tetrafluoromethane (CF4) are entirely negative, they are thereby unable to engage in σhole bonding interactions with the negative sites on another molecules. In this study, we have attempted at resolving this controversy by performing various high‐level electronic structure calculations with Quadra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
95
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(107 citation statements)
references
References 144 publications
(71 reference statements)
10
95
1
Order By: Relevance
“…Since the pioneering work by Brinck et al, many studies have used molecular electrostatic potential maps to demonstrate the σ‐hole in possible halogen‐bond donors, see for example references . Figure shows the electrostatic potential surfaces of the halogenated methyluracil molecules studied in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the pioneering work by Brinck et al, many studies have used molecular electrostatic potential maps to demonstrate the σ‐hole in possible halogen‐bond donors, see for example references . Figure shows the electrostatic potential surfaces of the halogenated methyluracil molecules studied in this work.…”
Section: Resultsmentioning
confidence: 99%
“…This has been attributed to the high electronegativity of fluorine and its tendency to engage in significant sp hybridization, which produces an influx of negative charge into the region where the positive σ‐hole would be . Some recent studies state that organic fluorines can form halogen bonds when strongly electronegative substituents are bound to the carbon . However, it has been suggested that this type of bond should not be labelled a halogen bond, as there are fundamental differences between these interactions and halogen bonds involving Cl, Br, and I .…”
Section: Introductionmentioning
confidence: 99%
“…The first, a halogen bond, which is formed when a positive region on the halogen in a molecule attracts a negative site (as in H 3 N•••F 2 , for example). The second, a σ‐hole, which is a region of deficiency of electron density on the electrostatic surface of the atom Y along the outer extension of the RY σ‐bond in molecules, which can be positive, negative, or neutral . The atom Y can be a halogen derivative X (X = Cl, Br, I), or any other main group element of the periodic table (mainly atoms of groups 14–17).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, an atom possessing a positive σ‐hole in a molecule can attract the negative site on another molecule to form an intermolecular noncovalent interaction. Such an attractive interaction has been referred to as either halogen bonding, or σ‐hole centered bonding …”
Section: Resultsmentioning
confidence: 99%
“…Despite these prior findings, the efficiency of the mPW1PW/6-31G * level was once more evaluated, within this new context, by comparison with the results obtained using a higher theory level that combines a long-range corrected hybrid functional, ωB97XD, with a much larger basis set, 6-311++G(2d,2p). The choice of this theory level was based on its well documented high performance regarding the description of hydrogen bonding [39][40][41][42].…”
Section: Computational Detailsmentioning
confidence: 99%